Cleaner production and drinking water: Perspectives from a scientometric and systematic analysis for a sustainable performance - Valdiviezo Gonzales, Lorgio Gilberto (2023)
Cleaner Production, as an environmental strategy, is integrated into processes, products, and services to increase efficiency and reduce risks to people and the environment. However, Cleaner Production management in water treatment services does not receive much public attention. To address this need, a scientometric analysis of the integration of Cleaner Production in water treatment was developed to investigate the efficacy and limitations of various Cleaner Production strategies applied in water treatment. A search was carried out in the Scopus database using the keywords "Cleaner production,’’ ``Wastewater treatment,’’ and ``Drinking water treatment’’ between January 1, 2002, and October 31, 2022. Through the scientometric analysis, it was possible to identify that Cleaner Production has been little applied in drinking water treatment. The reason for this was a systematic review of the application of Cleaner Production in drinking water treatment. The data and information obtained were filtered following the guidelines of the Preferred Reporting Declaration of elements for systematic reviews and meta-analyses (PRISMA). The PICO method was used to structure the important components of the research questions. The results of this review showed that there is currently little application of Cleaner Production in drinking water systems. This article concludes that Cleaner Production is a strategy that contributes to reducing the environmental impact generated by the different activities of treatment and distribution of drinking water. However, it is necessary to carry out research that promotes the dissemination and knowledge of the different Cleaner Production strategies, as well as highlighting the social, environmental, and economic benefits that their application could generate. Future research should aim at the application of Cleaner Production strategies such as water recycling and Good Housekeeping. Technological progress in purification processes can offer promising results for saving water, energy, waste reduction, and gaseous emissions.